PERAN GURU AGAMA DALAM IMPLEMENTASI PENDIDIKAN MODERASI BERAGAMA DI SDN 2 SUKODONO KABUPATEN JEPARA - Fajjariyah Itsna Ramadhani; Muhammad Misbahul Munir (Universitas Islam Malang, 2022)
The issue of discrimination, intolerance and similar practices should not be left alone, especially in a nation that has a high level of plurality like Indonesia. With this, it is necessary to present an institution called a school to manage and provide education and teaching to students in order to understand the reality of cultural, racial or religious differences. The concept of religious moderation education is a concept that provides a stimulus to students to understand the reality of religious differences. One of the schools that has religious diversity and implements religious moderation education is SDN 2 Sukodono, Jepara Regency. The purpose of this study was to describe the role of religious teachers in the implementation of religious moderation education at SDN 2 Sukodono, Jepara Regency. This research uses a field research approach. This type of research uses qualitative research that emphasizes the search for meaning, impact or phenomena with narrative presentation. Data collection techniques are interviews, observation and documentation. Data analysis uses Miles and Huberman analysis techniques, namely data reduction, data presentation and conclusion drawing. The result of this research is that the role of religious teachers at SDN 2 Sukodono, Jepara Regency contains three main roles, namely educator, teacher and facilitator. Meanwhile, the cultivation of the values ​​of religious moderation is manifested in intracurricular activities (classroom learning) and extracurricular activities (green school), and holiday celebrations.